Enhancing social sciences learning effectiveness with a learning management system - Budiman, Budiman; Supardi, Supardi; Sudrajat, Sudrajat (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2023)
This study aims to analyze the use of Learning Management System (LMS) in improving the eff ectiveness of Social Science (IPS) learning. This research uses the research method of literature study, which involves searching, selecting, and analyzing literature relevant to the research topic. The results of the analysis show that the use of LMS in social studies learning has great potential to improve learning eff ectiveness. LMS provides accessibility and fl exibility that allows students to access learning materials anytime and anywhere, overcoming space and time constraints. The interactive and collaborative features in the LMS facilitate interaction and collaboration between students and teachers, so students can share ideas, understanding, and experiences with fellow students and teachers. Through the LMS, teachers can monitor student progress in real-time and provide prompt feedback, which helps in the evaluation of learning. This research provides valuable insights for education practitioners in harnessing the potential of LMS to improve social studies learning.